The Negative Impact of COVID-19 in HCV, HIV, and HPV Surveillance Programs During the Different Pandemic Waves - Romero-Hernández, Beatriz; Martínez-García, Laura; Rodríguez-Dominguez, Mario; Martínez-Sanz, Javier; Vélez-Díaz-Pallarés, Manuel; Pérez Mies, Belen; Muriel, A.; Gea, Francisco; Pérez-Elías, María Jesús; Galán, Juan Carlos (Frontiers in Public Health, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic has been a worldwide stress test for health systems. 2 years have elapsed since the description of the first cases of pneumonia of unknown origin. This study quantifies the impact of COVID-19 in the screening program of chronic viral infections such as human papillomavirus (HPV), human immunodeficiency virus (HIV), and hepatitis C virus (HCV) along the six different pandemic waves in our population. Each wave had particular epidemiological, biological, or clinical patterns. Methods We analyzed the number of samples for screening of these viruses from March 2020 to February 2022, the new infections detected in the pandemic period compared to the previous year, the time elapsed between diagnosis and linking to treatment and follow-up of patients, and the percentage of late HIV diagnosis. Moreover, we used the origin of the samples as a marker for quantifying the restoration of activity in primary care. Results During the first pandemic year, the number of samples received was reduced by 26.7, 22.6, and 22.5% for molecular detection of HPV or serological HCV and HIV status respectively. The highest decrease was observed during the first wave with 70, 40, and 26.7% for HPV, HCV, and HIV. As expected, new diagnoses also decreased by 35.4, 58.2, and 40.5% for HPV, HCV, and HIV respectively during the first year of the pandemic. In the second year of the pandemic, the number of samples remained below pre-pandemic period levels for HCV (−3.6%) and HIV (−9.3%) but was slightly higher for HPV (8.0%). The new diagnoses in the second year of the pandemic were −16.1, −46.8, and −18.6% for HPV, HCV, and HIV respectively. Conclusions Undoubtedly, an important number of new HPV, HCV, and HIV infections were lost during the COVID-19 pandemic, and surveillance programs were disrupted as a consequence of collapse of the health system. It is a priority to reinforce these surveillance programs as soon as possible in order to detect undiagnosed cases before the associated morbidity-mortality increases. New pandemic waves could increase the risk of reversing the achievements made over the last few decades.